Experimental Study on Tribological Properties of Cu- Al2O3 Coated Ag nano Composite - Omyma El-Kady, Moustafa M. Mohammed, A. F. Meselhy, A. Wazeer, M. N. Elsheikh (International Journal of Advanced Science and Technology, 2020)
The present paper shows the experimental examination on the effect of Al2O3 coated Ag percent on the properties of Cu-Al2O3 coated Ag nanocomposites. With the object of enhancement wettability and dispersion of high weight fraction of Al2O3nanoparticles in Cu matrix, nano Al2O3particles were electroless coated via Ag particles. Four different Al2O3content, 3, 6, 9 and 12 wt.% were considered to highlight its effect on the properties of the produced nanocomposite. High energy ball milling is applied for mixing powders and compaction and sintering are applying for consolidation. Microstructural explanationsdisplayeda homogenous distribution of Al2O3. The relative density decreases with increasing the content of Al2O3 nanoparticles. In addition, microhardness is increased gradually via the addition of nano Al2O3 coated Ag. Sliding wear rate decrease via increasing the Al2O3 coated Ag nanocomposite content and increase with increasing the applied load. Also, the coefficient of friction decreases via increasing the nano Al2O3 coated Ag nanocomposite content.